Film Samsara: Representasi Alternatif Kritik Sosial dalam Wacana Modernitas - Aldira Dhiyas Pramudika (Program Studi Film dan Televisi Universitas Jember, 2023)
The aim of this research is to portray the function of documentary film as social criticism in modernity discourse. This research scrutinizes the poetic documentary film Samsara as the primary source of the study. The method used in this research is qualitative: the descriptive analysis through Michael Rabiger's documentary function theory. The label of 'alternative documentary' attached to poetic documentary film also becomes a focus of this study, especially the linkages of the delivery efficiency of the social issues. The result of this research reveals that image fragments represent the social issues in modernity discourse as follows: (1) Criminality, (2) Population, (3) Poverty, (4) Prostitution, and (5) Environment.